Organic Proton‐Buffer Electrode to Separate Hydrogen and Oxygen Evolution in Acid Water Electrolysis - Ma, Yuanyuan; Guo, Zhaowei; Dong, Xiaoli; Wang, Yonggang; Xia, Yongyao (Angewandte Chemie International Edition, 2019)
Hydrogen production from water via electrolysis in acid is attracting extensive attention as an attractive alternative approach to replacing fossil fuels. However, the simultaneous evolution of H2 and O2 requires a fluorine‐containing proton exchange membrane to prevent the gases from mixing while using the same space to concentrate the gases, which significantly increases the cost and reduces the flexibility of this approach. Here, a battery electrode based on the highly reversible enolization reaction of pyrene‐4,5,9,10‐tetraone is first introduced as a solid‐state proton buffer to separate the O2 and H2 evolution of acidic water electrolysis in space and time, through which the gas mixing issue can be avoided without using any membrane. This process allows us to separately consider H2 and O2 production according to the variation in input power (e.g., the renewable energy) and/or the location for H2 concentration, thus showing high flexibility for H2 production. A battery electrode of pyrene‐4,5,9,10‐tetraone is used as a solid‐state proton buffer to separate the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) during acidic water electrolysis in space and time, providing a flexible and membrane‐free architecture for electrochemical water splitting.